Structural Study on the Impact of Aerodynamic Loads on Winglet Support Structures - Morales, Eduardo; Chávez, Mario; Abarca, Griselda; López, Yunuén; Mares, Jesús; Cruz, Juan (International Journal of Engineering, Science and Information Technology, 2025)
Aerodynamic spoilers are intended to reduce drag forces and generate lift on surfaces. However, dynamic operating conditions can affect their performance and that of their supporting structures. This study evaluates the impact of aerodynamic loads on a spoiler's supporting structure using fluid-structure interaction (FSI) analysis. Three NACA airfoil models were analyzed to benchmark their structural behavior. Simulations using Ansys® software modeled the spoiler's airflow-induced pressures and structural displacements, considering dynamic loads derived from a similarity study between a full-scale (1:1) vehicle model and a scaled-down (1:6) version. The results revealed the mechanical behavior of the support under different flow conditions, assimilating the forces produced and how this is affected by the aerodynamics produced on the spoiler, generating data that informs the evaluation of this system and ensures reliability. The optimization of the support model allows for greater control over measurements, which is of great importance for wind tunnel testing, ensuring that evaluations are not affected by mechanical displacements of the support. The CAD model, combined with finite element Methods (FEM), allows visualization of the mechanical and aerodynamic behavior before manufacturing, thereby reducing the time and costs associated with physical testing and allowing critical failure points to be identified. The work includes studies through simulations of the aerodynamic and structural systems of the spoiler supports, generating data that helps understand and facilitate the evaluation of these systems and guarantees their reliability. Computational simulation is an essential tool for development and validation in the automotive sector.